An assessment of strategies that have been adopted to increase life assurance penetration in Zimbabwe - Mutero, Jacqueline (Midlands State University, 2017)
The Zimbabwean Insurance and Pension Commission (IPEC) aspire to reach a double digit penetration rate by end of year 2017. Therefore, this research intend to identify factors causing low life assurance penetration, assess the strategies adopted to increase the penetration rate by life assurance companies and recommend alternative strategies that can be implemented to increase life assurance in Zimbabwe. To achieve the set objectives, a descriptive research design was used to gather qualitative and quantitative data about the effectiveness of each strategy. A sample size of 55 respondents with 5 respondents from each company was used. A combination of stratified random sampling and judgemental sampling methods were employed for this study. The primary data was collected using personal interviews and questionnaires. The findings revealed that from the consumer side low life assurance consumption is caused by low income per capita, lack of trust and confidence in the public, low financial literacy or poor saving culture, lack of awareness about life assurance products among other causes. Causes emanating from the supplier side include inappropriate products, lack of reliable data, inadequate financial resources, limited distribution channels, lack of intellectual capital, to mention but a few. Among the strategies adopted micro-insurance, product innovation, bancaasurance, training of agents and aggressive marketing ranks as the most effective penetration strategies given the state of the country`s economic condition. The researcher recommend the following as alternative strategies that can increase life assurance penetration. Prioritisation in implementing strategies, human capital development, collaboration of life assurance companies with IPEC to raise awareness, a reform of the regulatory framework, strategic alliances, mergers and acquisitions as well as government intervention.